Ako ay may kiki i have a vagina - Oris, Glenda; Parrocha, Beth; Bravo, Becky; Rivera, Augie (Quezon City Lampara Publishing, Inc., 2023)
"Ang aking kiki ay bahagi ng katawan na tanging akin. Kaya lagi kong iingatan at pangangalagaan."
"My vagina is a part of my body that belongs to me and only me, and that's why I'll always take good care of it, and protect it."
"Rekomendado ang aklat na ito para sa mga batang edad 5 pataas."
"This book is recommended for children age 5 and up."
Text in Filipino and English.
"National children's book awards 2022. NCBA 2022 best reads. Mga premyadong kuwentong pambata."
Keywords: Vagina -- Care and hygiene; Vagina -- Care and hygiene -- Juvenile literature; Big books (Children's books).